2021
DOI: 10.3390/ijms22073733
|View full text |Cite
|
Sign up to set email alerts
|

The Photosystem II Assembly Factor Ycf48 from the Cyanobacterium Synechocystis sp. PCC 6803 Is Lipidated Using an Atypical Lipobox Sequence

Abstract: Photochemical energy conversion during oxygenic photosynthesis is performed by membrane-embedded chlorophyll-binding protein complexes. The biogenesis and maintenance of these complexes requires auxiliary protein factors that optimize the assembly process and protect nascent complexes from photodamage. In cyanobacteria, several lipoproteins contribute to the biogenesis and function of the photosystem II (PSII) complex. They include CyanoP, CyanoQ, and Psb27, which are all attached to the lumenal side of PSII c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…3b). 34 We found that Ycf48 bound to the lumenal regions of the D1 subunit via an Arg patch consisting of six residues (Ycf48-Arg180, Arg196, Arg215, Arg219, Arg220 and Arg237) (Fig. 3a, b, c).…”
Section: Interaction Of Ycf48 With D1 and D2mentioning
confidence: 78%
“…3b). 34 We found that Ycf48 bound to the lumenal regions of the D1 subunit via an Arg patch consisting of six residues (Ycf48-Arg180, Arg196, Arg215, Arg219, Arg220 and Arg237) (Fig. 3a, b, c).…”
Section: Interaction Of Ycf48 With D1 and D2mentioning
confidence: 78%
“…In general, the observed variance of the Psb27 lipid modification is typical for cyanobacterial lipoproteins since these proteins tend to bind lipids with different fatty acids (Fagerlund and Eaton-Rye 2011; Knoppová et al 2021;Nowaczyk et al 2006;Ujihara et al 2008), which originate from membrane phospholipids (Chattopadhyay and Wu 1977;Lai and Wu 1980). Therefore, the type of lipid modification is determined by the fatty acid composition of the membrane, which in turn changes depending on environmental conditions (Allakhverdiev et al 2001;Gombos et al 1997;Mironov et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacterial lipoproteins have been reported both in thylakoid and cytoplasmic membranes (Liberton et al 2016), but in contrast to the Sec-pathway itself (Liberton et al 2016;Nakai et al 1993;Srivastava et al 2005), a maturation pathway for lipidation was not yet identified in cyanobacterial thylakoid membranes (Agarwal et al 2010;Liberton et al 2016), apart from low abundant apolipoprotein N-acyltransferase. If the maturation system is not present in the thylakoid membrane, Psb27 and other photosynthesis related lipoproteins must be transferred efficiently after lipidation to the thylakoid membrane, as they are absent or only in low abundance in the plasma membrane (Ishikawa et al 2005;Knoppová et al 2021;Selão et al 2016). Alternatively, lipoproteins might be specifically modified in the PratA-defined membrane (PDM) region at the interface between plasma and thylakoid membrane (Rast et al 2016) and the transfer could be mediated by maturation centers, where both membranes (Rast et al 2019;Stengel et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that unusual PG containing PUFAs at the sn -2 position becomes a substrate for lipidation of these lipoproteins, which might affect the stability of the OEC. A recent study by Knoppová et al revealed that a PSII assembly factor, Ycf48, was lipidated by PG [ 41 ]. Therefore, the unstable PSII complex in the presence of PUFAs shown in Figure 3 might be due to the lipidation of Ycf48 by the unusual PG molecules.…”
Section: Discussionmentioning
confidence: 99%